Problem drinkers and high risk-taking behaviors under the stay-at-home policy of the COVID-19 emergency declaration - Mami Wakabayashi; Midori Takada; Aya Kinjo; Yoshifumi Sugiyama; Hiroyasu Iso; Takahiro Tabuchi (BMC, 2022)
Abstract Background To the best of the authors' knowledge, this is the first study to examine whether problem drinkers have had high risk-taking behaviors during the stay-at-home policy (e.g., dining out at a bar) under the COVID-19 emergency declaration. Methods We investigated data from Japan COVID-19 and Society Internet Survey(JACSIS)study-a web-based nationwide survey, conducted from August to September 2020. From a total of 12,076 current drinkers, problem drinkers were detected by Cut, Annoyed, Guilty, and Eye-opener (CAGE) questions. A CAGE score of 4 showed potential alcohol use disorder and scores of 2 to3 showed potential alcohol abuse; individuals with these scores were regarded as problem drinkers compared to light-or-no-risk drinkers, with a CAGE score of 0 to 1. The outcome assessed the presence of 18 behaviors against the stay-at-home policy, such as dining out at a bar, meeting people, or going to crowded places. All these behaviors were limited in Japan during the first declaration of emergency between April and May 2020. Results Based on the multivariable logistic regression, the participants with potential alcohol use disorder demonstrated 16 out of the 18 risk-taking behaviors, such as dining out at a bar (adjusted odds ratio (aOR): 2.08; 95% confidence interval (CI): 1.56-2.79), dining out at a restaurant (aOR: 1.79; 95% CI:1.37-2.35), visiting friends (aOR: 1.81; 95% CI: 1.34-2.44), going to karaoke (1.97; 95% CI: 1.26-3.10), and riding on a crowded train (aOR: 1.46; 95% CI: 1.07-1.99), compared to light-or-no risk drinkers with a CAGE score of 0 to 1. Additionally, participants with potential alcohol abuse (CAGE score of 2 to 3) had 10 out of 18 behaviors against the stay-at-home policy: the corresponding aORs for the aforementioned behaviors were 1.45 (95% CI: 1.25-1.67), 1.27 (95% CI: 1.12-1.44), 1.17 (95% CI: 1.01-1.36), 1.49 (95% CI: 1.17-1.90), and 1.19 (95% CI: 1.03-1.38), respectively. Problem drinkers had a significant association with being men, a higher income and job position, smoking, sleep deprivation, depression, and other mental diseases. Conclusions Overall, problem drinkers were more likely to have higher risk-taking behaviors against the stay-at-home policy, compared to light-or-no-risk drinkers.